Multiculturalism pro and Con: A criticism of the Liberal Perspective and Populist-Demagogical Denunciation - Pajnik, Mojca (Two Homelands, 2014)
Efforts towards the democratization of societies that respect differences have been focused in the last four decades in the European context but also world-wide around the notion of multiculturalism. The optimistic announcements of scholars who studied liberal multiculturalism in the period from the 1970s to the 1990s as alternatives to hierarchization, racism, discrimination and segregation of minority groups have been the frequent subject of criticism in the last two decades. While some take anapocalyptic, populist tone and speak about the end of multiculturalism, in the last couple of years we have witnessed a rise of counterarguments from proponents of multiculturalism who point to successful implementation of multiculturalism in practice. This article contrasts arguments and illustrates the entrapment of pro et contra positionings in debates. We defend the thesis that such an approach moves attention away from “problems with diversity”, is unable to overcome certain quandaries with regard to multiculturalism and also cannot generate new ideas towards a more egalitarian society. We devote particular attention to the defence of multiculturalism as presented in the most recent works of Will Kymlicka, one of the leading scholars of the liberal tradition of multiculturalism.